THE ROLE OF KPI AND OKR IN THE EFFICIENCY OF THE COMPANY - SEMENENKO, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article addresses the implementation and effective utilization of two crucial management methodologies - Key Performance Indicators (KPIs) and Objectives and Key Results (OKR) - in the context of the contemporary business environment. The significance of both methods is analyzed in the backdrop of increasing competition and constant industry changes, necessitating novel approaches to strategic management and the exploration of methods to enhance overall company efficiency. Various aspects of employing KPIs and OKRs in different types of companies and at various stages of their development are highlighted. Special attention is given to examining how both methodologies can coexist and interact to achieve maximum effectiveness in strategic management. A methodology for the joint implementation of KPIs and OKRs is proposed, taking into account the unique needs and characteristics of each approach. The outlined steps include analyzing the company’s strategy, identifying key areas for measurement, formulating specific objectives through OKRs, and determining corresponding KPIs. Roles and significance of Key Performance Indicators and Objectives and Key Results in different types of companies are analyzed, demonstrating how their combined usage can create synergy and ensure strategic success. The overall conclusion of the article underscores the importance of establishing an integrated management system that combines the stability of KPIs with the flexibility of OKRs. The necessity for continuous improvement and adaptation of these methodologies in the context of a dynamic business environment is emphasized. In summary, the article makes a significant contribution to understanding and applying strategic management methodologies, fostering the development of modern approaches to enhancing overall business efficiency.